The Gale encyclopedia of alternative medicine - Fundukian, Laurie J., 1970- (Gale virtual reference library, 2009)
Covers all aspects of the subject including therapies, conditions/diseases, herbs/plants, and people. Identifies numerous types of alternative medicine being practiced today, including reflexology, acupressure, acupuncture, chelation therapy, kinesiology, yoga, chiropractic, Feldenkrais, polarity therapy, detoxification, naturopathy, Chinese medicine, biofeedback, Ayurveda and osteopathy.